FRI0019 Peripheral blood neutrophils derived from patients with rheumatoid arthritis exhibit increased neutrophil extracellular trap formation. (23rd January 2014) - Papadaki, G.; Choulaki, C.; Mitroulis, I.; Verginis, P.; Repa, A.; Raptopoulou, A.; Boumpas, D.; Sidiropoulos, P.
Abstract : Background: Neutrophils are the most abundant cell type identified in the joints from patients with rheumatoid arthritis (RA), with a key role in inflammation and cartilage damage. Activated neutrophils form extracellular traps (NETs), with potent pro-inflammatory and immunostimulatory activity. Objectives: We sought to assess the role of NET release in RA pathogenesis. Methods: Peripheral blood neutrophils from active RA patients (n=6) (Disease activity score, DAS28 >5.1) and control subjects (n=7) were isolated. NET formation from RA neutrophils (peripheral blood/synovial fluid-derived) and control neutrophils treated with RA serum (n=7) or synovial fluid (n=7) was assessed by immunofluoresence microscopy, using co-staining with myeloperoxidase and 4', 6-Diamidino-2-phenylindole dihydrochloride (DAPI). The percentage of NET releasing cells was determined by examining 200 cells per sample in a double blind fashion. Time course experiments revealed optimal NET release at 3 hours. Results: Freshly isolated RA neutrophils from peripheral blood underwent spontaneous NET release at higher rates compared to normal controls (12±2.1% vs 3.21±0.9%, p<0.05). Interestingly, neutrophils derived from RA synovial fluid exhibited even higher rates of NETosis. Treatment of control neutrophils with either RA serum or RA synovial fluid increased NET release compared to cells treated with normal serum (16±2.5% or 9±1.5%, vs 3.2±0.7 p<0.005). Inhibition studies in progress address the impact of inflammatory cytokines and/or immune complexes in NET production, as well as the impact of NETs on dendritic and T cell activation. Conclusions: Neutrophil activation in RA is associated with enhanced NET formation, driven by soluble factors found in RA sera and synovial fluid. Whether NETs are involved in the cross-talk between neutrophils and adaptive immune responses in RA is under investigation. Disclosure of Interest: None Declared